(untitled) (Indonesian Economic Justice Review, 2025)
This paper explores the intersection of economic and racial justice in Indonesia, focusing on the disparities faced by ethnic minority groups in the country’s economic landscape. Indonesia’s diverse society is home to various ethnic groups, but historically, ethnic minorities such as the Chinese, Papuans, and Madurese have faced systemic discrimination that has hindered their access to economic resources and opportunities. This paper critically examines the economic marginalization of these ethnic groups, analyzing how racial prejudices and discriminatory policies have shaped their participation in the labor market, access to education, and entrepreneurial activities. By examining historical and contemporary examples of exclusionary practices, the paper highlights the role of state policies, cultural biases, and social structures in perpetuating these economic inequities. The paper also evaluates government measures aimed at addressing ethnic disparities, such as affirmative action programs, policies for indigenous land rights, and efforts to improve access to education and healthcare. The findings indicate that while some progress has been made, significant racial and economic disparities persist. The paper concludes by proposing policy reforms that focus on creating more inclusive economic opportunities, promoting diversity in the labor market, and ensuring that ethnic minorities are given equal access to economic resources and social services.